2007
DOI: 10.1007/s00264-007-0342-9
|View full text |Cite
|
Sign up to set email alerts
|

Cierny-Mader Type III chronic osteomyelitis: the results of patients treated with debridement, irrigation, vancomycin beads and systemic antibiotics

Abstract: Cierny-Mader (C-M) Type III osteomyelitis is defined as a localised lesion with both medullary and cortical involvement that is stable mechanically after debridement. The treatment of C-M Type III osteomyelitisis is difficult and requires a precise protocol to achieve a disease-free longterm follow-up. We report here the results of our study on 26 patients (19 men and 7 women; average age: 34.7 years) with C-M Type III osteomylelitis who were treated with radical debridement, irrigation, vancomycin-impregnated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
53
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 59 publications
(57 citation statements)
references
References 23 publications
2
53
0
2
Order By: Relevance
“…This study revealed that antibiotic embedded autogenous bone is not superior to débridement and parenteral antibiotic administration in implant-related infection. At this point we agree with Kinik et al that the quality of surgical débridement is the most important parameter for the success of treatment of bone infections [10].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This study revealed that antibiotic embedded autogenous bone is not superior to débridement and parenteral antibiotic administration in implant-related infection. At this point we agree with Kinik et al that the quality of surgical débridement is the most important parameter for the success of treatment of bone infections [10].…”
Section: Discussionsupporting
confidence: 92%
“…This result correlates well with recent literature. Many in vitro and in vivo studies have suggested that antibiotic-impregnated PMMA beads are very effective against eradication of infection [7][8][9][10][11]. However, antibiotic-impregnated PMMA beads have certain disadvantages.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies have focused on the effect of administering vancomycin systemically or using a local drug carrier method [2]. Moreover, studies show that MRSA is sensitive to high local concentrations of vancomycin, and the high success rate that was achieved is encouraging for the clinical use of vancomycin for MRSA-induced bone infections.…”
Section: Discussionmentioning
confidence: 99%
“…At present, the treatment of osteomyelitis primarily involves the surgical debridement of necrotic tissue, irrigation with an antiseptic solution, and the application of a course of systemic antibiotics for 6 weeks [1]. Vancomycin is recognized as an effective antibiotic against MRSA [2]. However, large doses of vancomycin do not penetrate efficiently into local sites due to the development of malformations secondary to the infection and may be associated with nephrotoxicity, ototoxicity, gastrointestinal side effects, increased costs, and low patient compliance.…”
Section: Introductionmentioning
confidence: 99%